How Differences Between Fashion Innovators and Non-Innovators Among Young People? - Novika Candra Astuti (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2016)
Fashion is important for our life because not only it allows you to dress fashionably but also help connect with people of same interest and provides as a form of entertainment. These days' youth are becoming so obsessed with fashion and mainly follow trends to get a sense of identity that they waste most part of their time and money on fashion. The purpose of this study is to identify the difference between innovators and non-innovator among young people in adopting new fashion item influenced by the selected determinants i.e. information seeking, variety seeking, product evaluation, price sensitivity, and hedonic shopping. This research also investigates shopping behavior and attitude among young consumers. Total 121 questionnaires were distributed among undergraduate students in Bandung. The result shows that price sensitivity and hedonic shopping significantly differentiate between fashion innovators and non-innovators. The results of the study provide guidance to designers and entrepreneurs in the fashion industry that greater focused on innovative consumers.Keywords: Fashion, Innovators, Non-Innovator, Young People